STRUCTURAL EQUATION MODELING OF CLEAN AND HEALTHY LIVING BEHAVIOR AMONG MOTHERS IN HOUSEHOLDS - Lisma Ningsih; Heru Laksono (Proceeding B-ICON, 2023)
The number of maternal deaths in Bengkulu Province for the last three years is still high, and Bengkulu City is one of the second highest contributors to maternal mortality. The purpose of this study was to determine whether the proposed theoretical model is suitable (fit) to explain the determinants of clean and healthy living behavior in mothers in the home setting in Bengkulu City in 2021. Quantitative research method with cross sectional research design. The research population is mothers who have toddlers in Bengkulu City, while the research sample is mothers who have toddlers who were chosen intentionally. The variable being measured is the latent variable, so it uses a structural equation modeling (SEM) application that examines the relationship between the variables as a unit. Clean and healthy living behavior (PHBS) in mothers in household settings in Bengkulu City is still low on the indicators of consumption of vegetables and fruit (8.7%) and non-smoking behavior (39.7%). The factor that plays the strongest role in shaping clean and healthy living behavior is perception. Clean and healthy living behavior can be improved if they have good knowledge, receive adequate social support, correct perception of clean and healthy living behavior and the availability of adequate sources of information. It is hoped that the Bengkulu City Health Office through the Coordinator of Midwives, Health Promoters and Cadres can encourage clean and healthy living behaviors in mothers by involving village officials or their peers so that together they improve clean and healthy living behaviors.